2013
DOI: 10.1089/vbz.2012.1011
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence of Crimean-Congo Hemorrhagic Fever Virus Infection in Hungary

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is a typical tick-borne pathogen that causes an increasing number of severe infections in many parts of Africa, Asia, the Middle East, and the Balkans, as well as in some other parts of Europe. The virus is transmitted primarily by Hyalomma spp., and the spectrum of natural hosts for CCHFV is broad, including wild and domestic animals. Although, the presence of CCHFV was hypothesized in Hungary, no significant research activity has been carried out in the past 30 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…The prevalence we found here (0.58-1.16%) is similar to that reported in the 1980s by Filipe et al in southern Portugal [23]. It is also similar to the prevalence found in other European countries with a very low or null incidence, such as Hungary [35] or Greece [36]. Even though the seroprevalence in the general population in Greece is close to 3.5%, (with an unexpectedly high seroprevalence > 15% in individuals involved in animal husbandry for work), these values contrast with the low incidence of the disease on the Greek territory (only one symptomatic and fatal case has been reported since 2008) [36].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence we found here (0.58-1.16%) is similar to that reported in the 1980s by Filipe et al in southern Portugal [23]. It is also similar to the prevalence found in other European countries with a very low or null incidence, such as Hungary [35] or Greece [36]. Even though the seroprevalence in the general population in Greece is close to 3.5%, (with an unexpectedly high seroprevalence > 15% in individuals involved in animal husbandry for work), these values contrast with the low incidence of the disease on the Greek territory (only one symptomatic and fatal case has been reported since 2008) [36].…”
Section: Discussionsupporting
confidence: 92%
“…Other countries in central Europe, such as Hungary, are not considered endemic for this infection, though seropositivity for CCHFV antibodies has been described since 1976 [46]. Recent studies have shown that this zoonosis is also circulating in animals in countries such as Romania and the former Yugoslav Republic of Macedonia [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…In 1969, it was recognized that the pathogen causing the Crimean haemorrhagic fever and the Congo haemorrhagic fever were serologically indistinguishable and linkage of these two place names resulted in the current name for the disease and the virus (Casals, 1969;Whitehouse, 2004;Gao et al, 2010;WHO, 2011;Wu et al, 2013). CCHF is one of the deadly hemorrhagic fevers that are endemic in Africa, Asia, Russia, Europe, and the Middle East and being zoonotic, it is of public health concerns in many countries of the world (Mardani and Keshtkar-Jahromi, 2007;Flusin et al, 2010;Chinikar et al, 2010;Appannanavar and Mishra, 2011;Ergonul, 2012;Leblebicioglu et al, 2012;Lobermann et al, 2012;Bente et al, 2013;Oncu, 2013;Nemeth et al, 2013). The surveillance of the virus is difficult in Africa, due to limited sanitary facilities.…”
Section: Epidemiologymentioning
confidence: 99%